Elaborating the Three: the Functions of Autobiographical Memories Related to Discrimination and Identity Undermining Experiences - Yilmaz, Ayce Feride; Boyacioglu, Inci (SPRINGERNATURE, 2024)
This paper aims to contribute to the extant autobiographical memory functions research, which predominantly involves three theoretical constructs being directive, self, and social, mostly tackled on the individual level. In making the general call for foregrounding social identity-related memory functions as a relevant object of study, the present study relies on a particular memory type, that is, of discrimination and denigration against one's ethnoreligious identity. Findings of interviews with a total of 9 Armenian, Kurdish, and Alevite participants in Turkey reveal in each of the theoretically insulated domains, the real-world operation of these memories renders intertwined functions both on the individual and group level. Particularly, social memory exchanges manifest peculiar constructs pointing at social identity-linked outcomes. As scholarly appeals for investigating autobiographical memory functions' lived intersectionality continues, this research addresses this agenda for elaborating isolated theoretical considerations revealing memories' versatile social identity-related usages on individual and group levels.
Keywords: Autobiographical memory; Autobiographical memory functions; Discrimination; Social identity; Social group; SELF; SILENCE; CONSEQUENCES; CONFLICT; EMOTIONS; POLITICS; TRAUMA; Psychology